PEMBUATAN ALAT BANTU PEMOTONGAN SARI KELAPA PADA INDUSTRI KECIL PEDESAAN - Hadi, Setya; Nurdjito, Nurdjito (Universitas Negeri Yogyakarta, 2004)
Introduction. UD. Kencana Gading Gejayan Condong Catur, begun his work in coconut business, than he thought to use the water of coconut as object of his business too. Now, the production of decoco is not enough for the market, because he slices it with knife. It makes slowly, and the product is not reguler in shape and the size.This program has an objective to make a slice device to a pieces of decoeo tobe small one regularly, clean,wealthy, easy to do, and rapidly, so the partner will be able to raise his product.This Program offers the slice method with electrical slice device. It may slice more reguler, easy, quickly, and made of stainless steel sheet, the processes include: survey the appropriate material, the size of decoco, the condition of shop and what' needed b;: the shop, to design the slice device, to plan the processes, to get ready the material and the tools, to make the slicer, to test and to make it more better, to get partner's opinions, and to complete the design.Conclusion. This Program helps UD. Kencana Gading to get a slicer that will raise the product of decoco, from 250 to 600 kg in one day, in reguler size that is 1.2 ern, to gain the added values Rp 1.919.775, in every month. The slicer has capacity]200 kg in a day, powered by electrical motor 0,25 hp, 1420 rpm, easy to handling and to maintenance.